2020
DOI: 10.1186/s13104-020-05407-5
|View full text |Cite
|
Sign up to set email alerts
|

Supportive care: men’s expectations who undergoing in vitro fertilization treatment

Abstract: Objective Infertile couples perceive some needs and expectations during treatment. Most studies have focused on infertile women’s needs. The study was done to explore the expectations of men who undergoing in in vitro fertilization (IVF) treatment. Participants were men whose wives undergo IVF treatment in the IVF clinic of Shahid Motahhri hospital in Urmia. Purposive sampling was performed and data collection was done through in-depth semi-structured interviews until data saturation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…The review revealed that many men undergoing ART felt passive and uninvolved in the process compared with their partners 32 . Moreover, they reported feeling little help during the treatment 3,26,29,30,33–36 . Moreover, the process of semen collection was perceived to be embarrassing and uncomfortable, with the semen collection room being poorly located and inconducive 37,38 .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The review revealed that many men undergoing ART felt passive and uninvolved in the process compared with their partners 32 . Moreover, they reported feeling little help during the treatment 3,26,29,30,33–36 . Moreover, the process of semen collection was perceived to be embarrassing and uncomfortable, with the semen collection room being poorly located and inconducive 37,38 .…”
Section: Resultsmentioning
confidence: 99%
“…In addition, studies by Cipolletta and Faccio, 31 Schick et al, 30 Ying et al, 13 and Bayrami et al 33 highlighted that several men felt a sense of helplessness as they went through the treatment without being considered or involved in the decision‐making process. This led to some feeling the need for psychological support 33 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations